2022
DOI: 10.1111/imm.13557
|View full text |Cite
|
Sign up to set email alerts
|

Fc Fragment of IgE Receptor Ig (FCER1G) acts as a key gene involved in cancer immune infiltration and tumour microenvironment

Abstract: Although recent studies have revealed the relationship between Fc Fragment of IgE Receptor Ig (FCER1G) and human tumours, there is still a lack of a more comprehensive pan-cancer analysis of FCER1G as an immune-related gene. In this study, we investigated the expression pattern and prognostic value of FCER1G based on multiple databases. Subsequently, we further explored the role of FCER1G in tumour proliferation and metastasis, as well as its genomic alterations and DNA methylation levels, we next assessed the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…FCER1G is an important inflammation-related molecule that encodes the Fc receptor γ-chain (FcRγ). FcRY contains an immune receptor tyrosine-based activator motif (ITAM) which is a key signaling transducer of multiple pathways mediating autoimmunity and chronic inflammation [33]. Numerous studies have found that FCER1G is expressed on the surface of various immune cells, including neutrophils, macrophages, eosinophils, etc., [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…FCER1G is an important inflammation-related molecule that encodes the Fc receptor γ-chain (FcRγ). FcRY contains an immune receptor tyrosine-based activator motif (ITAM) which is a key signaling transducer of multiple pathways mediating autoimmunity and chronic inflammation [33]. Numerous studies have found that FCER1G is expressed on the surface of various immune cells, including neutrophils, macrophages, eosinophils, etc., [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…The expression of FCER1G increases within many cancers. FCER1G expression was positively associated with tumor prognostic outcome, growth, and migration; also, FCER1G was closely related to tumor immunity and tumor microenvironment (TME) [ 33 ]. FCGR3A usually shows upregulated in pan-cancer [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, for gliomas of the central nervous system, the results were reversed 32 . The results 33 , 34 of two pan-cancer studies suggest that FCER1G is involved in the immune infiltration process of tumors and may be a potential immunotherapeutic target. Our experiment confirmed that it was highly expressed in the sinuses of normal tissue adjacent tumor, while the expression of tumors was reduced.…”
Section: Discussionmentioning
confidence: 99%